The Distribution of Political Power of Karaeng in Jeneponto - Syarifuddin, Syarifuddin; Jumadi, Jumadi; Muhammad Syukur; Syamsu A Kamaruddin (Tinta Emas Publisher, 2025)
This study examines the distribution of political power within the social structure of Karaeng in Jeneponto, South Sulawesi. As a local entity with a strong history of traditional power, Karaeng plays an important role in the social structure, governance, decision-making, policy formulation, and social control. This research aims to understand how political power is distributed by the Karaeng group within the government structure and how this influences the social structure and local political dynamics. A qualitative approach is used in this study, with in-depth interviews and literature review as the primary data collection techniques. The results show that the distribution of political power carried out by Karaeng within the government structure is strongly influenced by factors such as lineage, kinship, social networks, social status, and strong patron-client relationships, all of which contribute to the significant influence of Karaeng in local politics in Jeneponto.